2019
DOI: 10.1155/2019/1538273
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Investigation into Formation of Metro Wheel Polygonalization

Abstract: We present a detailed investigation of the mechanism of metro wheel polygonal wear using on-site experiments and numerical simulation. More than 70% of metro wheels exhibit 6th–8th harmonic-order polygonal wear; the excitation frequency of the polygonal wear is located in the 50–70 Hz interval at an operating speed of 65–75 km/h. To determine the root cause of the polygonal wear, a dynamic train behavior test is conducted immediately after wheel reprofiling. The results suggest a natural mode resonance in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 40 publications
(69 reference statements)
0
18
0
Order By: Relevance
“…15, which is caused by the P2 resonance. The formation mechanism of the wheel OOR reported in [14] was further verified by numerical simulation performed by our research team [75]. Through field investigation, Li et al [17] pointed out that polygonal wear with 7 harmonics in one metro line was also caused by the P2 resonance.…”
Section: P2 Resonancementioning
confidence: 53%
See 2 more Smart Citations
“…15, which is caused by the P2 resonance. The formation mechanism of the wheel OOR reported in [14] was further verified by numerical simulation performed by our research team [75]. Through field investigation, Li et al [17] pointed out that polygonal wear with 7 harmonics in one metro line was also caused by the P2 resonance.…”
Section: P2 Resonancementioning
confidence: 53%
“…Kalousek and Johnson [8] (2) P2 resonance Nielsen et al [5], Johansson and Andersson [74], Tao et al [14], Li et al [17], and Cai et al [75] (3) Frictional self-excited vibration of a wheelset-track system Chen et al [76,77], Zhao et al [78], and Wu et al [79] (4) Lower bending or torsional modes of the wheelset Morys [20], Jin et al [80], Yang et al [15], Tao et al [16,[81][82][83], Fröhling et al [84], and Spangenberg [85] (5) Bending vibration modes of the rail or track Johansson and Andersson [74], Wu et al [86], Cai et al [87], Dai et al [88], and Qu et al [89] (6) Excited resonance of the bogie Wu et al [90] and Guo et al [91] (7) Vibration of other components of the bogie Ma et al [92], Liu et al [93], and Fu et al [94] 3. Thermoelastic instability Nielsen et al [5] (Summary) and Vernersson [95,96] with three harmonics.…”
Section: Induced By Initial Wheel Defectsmentioning
confidence: 99%
See 1 more Smart Citation
“…erefore, the vertical deflection of the rail is discussed in detail here, and the equations of lateral and torsional deflection can refer to [9,14,28].…”
Section: Finite Long Slab Track Modelmentioning
confidence: 99%
“…By considering the real wheel out-of-roundness, the considerably fluctuating wheel/rail contact force was observed from a vertical vehicle-track coupled dynamics model [17]. Similarly, by using on-site experiments and simulations, the mechanism of metro wheel polygonal wear was carefully explored at the speed of 65-75 km/h and suggested that the wheelset flexibility could accelerate the polygonal wear and abnormal vibration [19,20]. Such an irregular wheel profile was reasonably believed to produce a detrimental effect on the railway axle and bogie frame [21][22][23].…”
Section: Introductionmentioning
confidence: 99%